Chemical characterization and antioxidant capacity of red radish (Raphanus sativus L.) leaves and roots. (June 2015) - Goyeneche, Rosario; Roura, Sara; Ponce, Alejandra; Vega-Gálvez, Antonio; Quispe-Fuentes, Issis; Uribe, Elsa; Di Scala, Karina
Highlights: Red radish roots and leaves were phytochemical characterized. The nutritional value of radish leaves far exceeded the value for roots. TPC and total flavonoid levels of leaves were almost two and four times higher than roots. Radish leaves have shown excellent antioxidant capacity. Red radish roots and leaves are important sources of bioactive compounds. Abstract: Red radish roots and leaves were characterized in terms of their physico-chemical, nutritional, antioxidant and microbiological properties. The nutritional value of radish leaves far exceeded the corresponding value for roots. Leaves presented higher percentage of protein, ash and crude fiber than roots. Calcium was found to be the most abundant mineral with a value of 752.64 mg/100 g. Ascorbic acid content in leaves (38.69 mg/100 g) doubled the value found in roots. Total phenolic contents of leaves (695.07 mg GAE/100g d.m.) were almost two times higher than for roots, while total flavonoid levels (1042.73 mg quercetin/100 g d.m.) were four times higher. Leaves' and roots' antioxidant activities were 39.48 mmol and 11.09 mmol TE/100 g d.m., respectively, by means of ORAC analysis. The most abundant free and bound phenolic compounds of roots and leaves were pyrogallol and vanillic acid; and epicatechin and coumaric acid, respectively.